2017
DOI: 10.1002/dac.3464
|View full text |Cite
|
Sign up to set email alerts
|

Artificial noise–aided secure communication in a bidirectional relaying network

Abstract: An artificial noise strategy is proposed for amplify-and-forward bi-directional relay network where the eavesdropper can wiretap the relay channels in both hops. Artificial noise is used to confuse the eavesdropper and improve its secrecy.Specifically, the source and the relay are allowed to split their available transmit power into 2 parts: a useful information portion and a jamming portion to transmit a jamming signal. The mathematical model is established for 2-way relay network with an eavesdropper. The se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In Zhou et al, 26 a comparison between one-way and two-way half-duplex AF relaying schemes with an untrusted relay is studied in terms of their secrecy rates, and it is found that with equal transmit power at the two relaying protocols, the two-way relaying scheme has better performance compared with one-way relaying protocol under high SNR regime. In Li et al, 27 an AN-aided jamming strategy is exploited to improve the secrecy rate of a two-way AF relay network in the presence of an eavesdropper, employing power allocation at the source and relay. The authors in Deng et al 28 investigate the secure communications of multiuser untrusted AF relay networks considering direct links where one user is selected with the help of an untrusted relay.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Zhou et al, 26 a comparison between one-way and two-way half-duplex AF relaying schemes with an untrusted relay is studied in terms of their secrecy rates, and it is found that with equal transmit power at the two relaying protocols, the two-way relaying scheme has better performance compared with one-way relaying protocol under high SNR regime. In Li et al, 27 an AN-aided jamming strategy is exploited to improve the secrecy rate of a two-way AF relay network in the presence of an eavesdropper, employing power allocation at the source and relay. The authors in Deng et al 28 investigate the secure communications of multiuser untrusted AF relay networks considering direct links where one user is selected with the help of an untrusted relay.…”
Section: Introductionmentioning
confidence: 99%
“…Adopting the transmission scheme in An et al 24 to the proposed model, the three scenarios are studied under two cooperative schemes; AF without and with artificial noise (AN) and their secrecy performance is compared with direct transmission schemes. Here, the main focus is on relay selection; however, the proposed algorithm can be further modified and applied for two-way relay communication 26,27 employing cooperative trusted or untrusted relays.…”
Section: Introductionmentioning
confidence: 99%